Pengaruh Persepsi Kemudahan, Keamanan dan Manfaat Terhadap Minat Menggunakan Dompet Digital Dana dengan Literasi Keuangan Syariah Sebagai Variabel Moderating pada Masyarakat di Telanaipura Kota Jambi - Sumarni Sumarni; Usdeldi Usdeldi; Anzu Elvia Zahara (Pusat Riset dan Inovasi Nasional, 2026)
This study investigates the influence of convenience, security, and benefits on the interest in using the DANA e-wallet, with Islamic financial literacy as a moderating variable in Telanaipura, Jambi. This is a quantitative study to investigate the use of the DANA e-wallet in Telanaipura. The sampling technique used a non-probabilistic sample with a sample size of 100 people. Data analysis and processing in this study used descriptive statistical methods through structural equation modeling (SEM) with partial least squares analysis (SEM-PLS). The results of this study indicate that the perceived convenience variable has a significant influence on the interest in using the DANA e-wallet in Telanaipura, Jambi, and the security variable has a significant influence on the interest in using the DANA e-wallet in Telanaipura, Jambi. The perceived benefits variable has a significant influence on the interest in using the DANA e-wallet in Jambi City, Telanaipura, while the